Improving multi-sectoral nutrition coverage measurement: The One Nutrition Coverage Survey in Bangladesh - Manohar, Swetha; Nguyen, Phuong Hong (DataDENT, 2025)
Over the last two decades many low-and-middle-income countries (LMICs) have developed multi-sectoral nutrition policies to address high rates of malnutrition across their populations. As of 2022, 45 out of 66 Scaling Up for Nutrition (SUN) countries have a national multi-sectoral nutrition policy, the remaining countries are working towards such policies. However, few countries have sufficient data on the reach or coverage of nutrition interventions across sectors to effectively monitor and support multisector policy implementation.